Risk factors for low bone density in pediatric nephrotic syndrome - Corina Lisa; Madarina Julia; Pungky A. Kusuma; Tonny Sadjimin (Paediatrica Indonesiana, 2011)
Background Disturbances in bone mineral metabolism and sideÂ effects of corticosteroid treatment may cause decreased boneÂ density in patients v.ith nephrotic syndrome (NS).Objectives To compare the prevalence oflow bone mineral densityÂ (BMD) in children with and 'Without NS and to assess the effectÂ of corticosteroid treatment on bone density in NS patients.Â Methods We conducted a retrospective, cohort study in childrenÂ aged 5-18 years diagnosed 'With NS for more than 2 months prior toÂ data collection, and in children v.ithout NS as a control. BMD wasÂ assessed on calcaneal bone wlith ultrasound bone densitometry.Â Serum calcium, albumin, creatinine and phosphate levels wereÂ also assessed.Results The prevalence of low BMD was significantly higher inÂ NS patients than nonô€‚NS subjects, 73.3% (22 in 30) vs. 33% (11Â in 33), respectively. The prevalence ratio was 6.3 (95% CI 2.1Â to 18.9). NS patients had lower serum calcium levels, With meanÂ difference of -0.17 (95% CI -0.27 to -0.07 mMollL), P<0.009, andÂ lower serum albumin, with mean difference of Â -0.88 (95% CI -1.27 to -0.49 gIL); P<O.OO 1, than nonô€‚NS subjects. After adjusting forÂ other risk factors, we found NS to be an independent risk factor forÂ low BMD. Steroid-resistant and steroid-dependent patients hadÂ lower BMD than steroid-sensitive subjects (P=0.02). There wasÂ also a significant correlation between the onset of corticosteroidÂ treatment and BMD (r=O.3; P=0.02).Conclusions NS patients had higher risk for low BMD comparedÂ to normal subjects. Response to steroid treatment influencesÂ the severity of impaired bone density.